PERANCANGAN MODEL SIMULASI PADA KASUS SISTEM TRANSPORTASI DENGAN MENERAPKANNYA PADA ARUS LALU LINTAS - Oryza Pratama; Vicko Rizkyadi, Rezkyan Dharen Fadilah, Jeremy Valetino, Paduloh (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
As the transportation system continues to improve and competition between transportation modes increases, the number of public transport passengers will continue to increase, causing congestion. Congestion, both natural and human-induced, is a factor that greatly affects the efficiency of the transportation system. In this article, traffic flow on a highway often causes congestion due to the presence of passing vehicles, which can result in an increase in the number of vehicles using the highway, resulting in congestion. A poorly designed transportation system can cause vehicle queues on the highway. The vehicle congestion that occurs on the highway is not the congestion that occurs on the server, so the problem of vehicle congestion cannot be solved only by congestion theory methods. This shows that the system under study is a complex system. The complexity of the problem in modeling the system shows the need for a simulation model. This article presents a simulation model of a vehicle traffic system using an agent-based and object-oriented simulation model. The modeled vehicle can predict the movement steps of other vehicles whose trajectories intersect with the vehicle.